CLINICAL ANALYSIS OF A DIGITAL METHOD FOR RADIOGRAPHIC ROOT CANAL LENGTH DETERMINATION - Narcis M. Marcov; Elena-Cristina G. Marcov (Romanian Society of Oral Rehabilitation, 2013)
Aim of the study The objective of this analysis was to investigate a digital method for radiographic working length determination. Material and methods 300 scanned periapical radiographs for 240 clinical cases with undergoing endodontic treatment had the working length digitally measured using a distance measurement program. A mathematical algorithm of calculus based on proportionality ratio between clinical and radiological dimensions of dental crown and root was used for each tooth. The data (before and after treatment) obtained for each analysed case from 10 observers were used to evaluate the accuracy of the method for each group of teeth. Results The mean determinations for initial and postoperative working length were in the range of the golden standard provided by the statistical data. The accuracy of the method varied for the pre and post treatment measurements in a direct correlation with the root particularities (degree of curvature, apex spatial orientation). Conclusions The results of this study suggest that the digital measurement tool combined with an appropriate algorithm of calculus can be used for clinical working length determination regardless the morphological endodontic particularities.